O037 Genioglossus motor control following the return to sleep after brief arousal. (7th October 2021) - Dawson, A; Avraam, J; Nicholas, C; Kay, A; Trinder, J; Jordan, A
Abstract: Rationale: Arousal from sleep has been shown to elicit a prolonged increase in genioglossus muscle activity that persists following the return to sleep and may protect against airway collapse. We hypothesised that this increased genioglossal activity following return to sleep after an arousal is due to persistent firing of inspiratory single motor units (SMUs) recruited during the arousal. Methods: 34 healthy participants were studied overnight while wearing a nasal mask/pneumotachograph to measure ventilation and with 4 intramuscular genioglossus SMU electrodes. During stable N2 and N3 sleep, auditory tones were played to induce brief (3-15s) AASM arousals. Ventilation and genioglossus SMUs were quantified for 5 breaths before the tone, during the arousal and for 10 breaths after the return to sleep. Results: A total of 1089 tones were played and gave rise to 236 SMUs recorded across arousal and the return to sleep in 20 participants (age 23±4.2 years and BMI 22.5±2.2kg/m2). Ventilation was elevated above baseline during arousal and the first post-arousal breath (p<0.001). The peak firing frequency of expiratory and tonic SMUs was unchanged during arousal and return to sleep, whereas inspiratory modulated SMUs were increased during the arousal and for 4 breaths following the return to sleep (p<0.001). Conclusions: The prolonged increase in genioglossus activity that occurs on return to sleep after arousal is a result of persistent activity of inspiratory SMUs. Strategies to elevate inspiratory genioglossus SMU activity may be beneficial in preventing/treating obstructive sleep apnea.